HIGH PREVALENCE OF METABOLIC SYNDROME IN SIBERIAN MEN WITH CORONARY ATHEROSCLEROSIS - M. I. Voevoda; Yu. I. Ragino; A. M. Chernyavsky; S. Yu. Tsymbal; E. V. Semaeva; Ya. V. Polonskaya; M. V. Ivanova (Российский кардиологический журнал)
In 42-70-year-old Siberian men with coronary atherosclerosis, verified by coronary angiography, the prevalence of metabolic syndrome (MS) was as high as 89%, which suggests an important role of MS in atherosclerosis development in the Siberian region. In pre-existing coronary atherosclerosis, biomarkers of inflammation and destruction (highly sensitive C-reactive protein, inflammatory cytokines, and destructive metalloproteinases) correlated with MS components, reflecting the pathophysiological role of inflammation in MS development.